Den sovjetiske Nordflåtens operasjonsplaner (1939-1940) - Holtsmark, Sven G.; Petrov, Pavel V. (Septentrio Reports, 2020)
The present report contains a selection of documents on the Soviet Northern Fleet's operational planning 1939–1940. Dr Pavel V. Petrov has collected the documents from the Russian State Naval Archive in St Petersburg. They are translated into Norwegian and annotated by Professor Sven G. Holtsmark. Holtsmark and Petrov have written a broad introductory essay on the role of the European far north in russian policy and strategy in the interwar period. The project was conducted within the research programme "In a world of total war: Norway 1939–1945". Rapporten består av et sentralt utvalg av den sovjetiske nordflåtens operasjonsplaner for 1939–1940. Dr. Pavel V. Petrov har hentet dokumentene fra det russiske marinearkivet i St. Petersburg . De er oversatt til norsk og annotert av professor Sven G. Holtsmark. Holtsmark og Petrov har skrevet en bredt anlagt introduksjon som tar for seg nordområdenes plass i sovjetisk militær tenkning i perioden. Arbeidet er utført som en del av forskningsprogrammet "I en verden av total krig: Norge 1939–1945", ledet av UiT Norges arktiske universitet.